The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.2466/pr0.1997.80.3.744
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of the Vengeance Scale

Abstract: Further validation of the Vengeance Scale was explored. Scores on the scale were significantly and positively correlated with measures of hypermasculinity and inversely correlated with personal values of kindness and self-control for 25 men; however, college women's scores did not correlate significantly with either kindness or self-control. Further research is needed to assess whether the scale is valid for men as well as women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Stuckless and Garonson (1992) demonstrated that the Vengeance Scale was negatively related to empathy and positively related to trait anger. Previous studies have confirmed its external validity (Holbrook, White, & Hutt, 1995) and convergent validity (Hutt, Iverson, Bass, & Gayton, 1997). Therefore, the scale was translated into Japanese in order to examine associations among vengeance, trait anger, and empathy.…”
mentioning
confidence: 98%
“…Stuckless and Garonson (1992) demonstrated that the Vengeance Scale was negatively related to empathy and positively related to trait anger. Previous studies have confirmed its external validity (Holbrook, White, & Hutt, 1995) and convergent validity (Hutt, Iverson, Bass, & Gayton, 1997). Therefore, the scale was translated into Japanese in order to examine associations among vengeance, trait anger, and empathy.…”
mentioning
confidence: 98%
“…I measured vengefulness using the 20-item Vengeance Scale (VS) developed by Stuckless and Goranson (1992). Previous researchers have demonstrated the measure's reliability, fi nding internal consistency and test-retest reliability coeffi cients typically exceeding .80 (Brown, 2004;Holbrook, White, & Hutt, 1995;Hutt, Iverson, Bass, & Gayton, 1997). The measure's fi nal score ranges from 20 to 140, with higher scores representing a stronger endorsement of vengeful attitudes.…”
Section: Methodsmentioning
confidence: 99%
“…Vengeance also correlates significantly with greater machismo: an exaggerated sense of masculinity (Hutt et al, 1997;Sommers, 2000). This phenomenon sheds light on the three cases in which boys shot other boys who directly threatened their relationship with girls who were important to them.…”
Section: Jealousy/protectionmentioning
confidence: 94%
“…Research shows that males sometimes attribute their acts of violence to jealousy (Bookwala et al, 1992;Stamp and Sabourin, 1995;Holtzworth-Munroe et al, 1997;Sommers, 2000) and studies pertaining to intimate violence cite jealousy as a common motive for murder (Sommers, 2000). Vengeance also correlates significantly with greater machismo: an exaggerated sense of masculinity (Hutt et al, 1997;Sommers, 2000). This phenomenon sheds light on the three cases in which boys shot other boys who directly threatened their relationship with girls who were important to them.…”
Section: Jealousy/protectionmentioning
confidence: 99%